Effectiveness of Growing Media on the Growth of Stem Cuttings of Ficus benjamina in Ketapang, West Kalimantan - Eti Artiningsih Octaviani; Oktarina Maulidia; Muhammad Reza; Vilda Puji Dini Anita; Robithotul Huda; Septian Faris Al-Amin (Jurnal Biologi Tropis, 2026)
Peat swamp forests in Indonesia face significant pressure due to ecosystem degradation. One example is in Ketapang Regency, West Kalimantan. Restoration efforts are needed to restore ecosystem function,  including revegetation with Ficus benjamina, which is adaptive to peatland conditions. The  restoration success rate is expected to improve with the use of. This study aimed to evaluate the effectiveness of different growing media on the growth performance of F. benjamina stem cuttings. This study used a completely randomized design (CRD) with 5 planting media treatments (P0–P4) and 8 replications. Parameters included plant height, stem diameter, number of leaves, and changes in soil chemical properties (pH and organic carbon), with supporting data of temperature, humidity, and rainfall as environmental factors. The results showed that planting media treatments significantly affected the vegetative growth of F. benjamina. Treatment P4 (peat + rice husk charcoal + compost) produced the best growth with an average height of 14.60 cm, stem diameter of 2.33 mm, and number of leaves of 8, compared to the control (P0) with a height of 11.25 cm, diameter of 1.11 mm, and 6 leaves. Furthermore, soil pH increased from acidic (4.6–5.0) to neutral (6.5–6.7). These results indicate that  combining planting media with organic matter effectively improves soil chemical properties and supports the growth of F.benjamina, thus offering potential for application in peatland restoration.